TEOR DE ÓLEO NA CULTURA DA SOJA EM FUNÇÃO DE FONTES E DOSES DE FÓSFORO - Souza, Nátali Maidl de (2012)
Increasing use of vegetable oils as fuels has led to studies that seek to qualify these raw materials. In the case of soybean, genotype, soil and climatic cropping conditions, and agronomic management are reported as responsible by oil content, protein and fatty acid profile variation. The aim of this study was to determine the influence of phosphorus fertilization on oil content produced by soybean crop, and also effects on grain yield, weight of 100 seeds, oil yield, protein content, protein yield, content of phosphorus and phosphorus accumulation in the grain. The work was carried out in the years 2010/2011, under randomized blocks experimental design, with four replications, in a factorial scheme 3 x 3, with three sources (triple superphosphate, phosphate rock and magnesium termophosphate) and three rates of phosphorus (60, 120 e 180 kg ha-1 of P2O5) placed before soybean sowing (Apolo genotype), in the autumn/winter crop season, besides one additional treatment for each source, placed during the spring/summer crop season, at a 90 kg ha-1 of P2O5 (local control). There were no significant effects of sources and rates of phosphorus, applied earlier, on grain yield, weight of 100 seeds, oil content, oil yield, protein content and protein yield. For P content, triple superphosphate was superior than phosphate rock, and rates from 120 kg ha-1 were superior than the lowest rate. Phosphorus accumulation was higher in triple superphosphate and magnesium termophosphate sources, where the rate of 120 kg ha-1 of P2O5 was superior than the lowest rate. The contrast between the fertilization placed in autumn/winter and spring/summer crop seasons showed effect on protein content, where fertilization placed in spring/summer crop season showed superior effect, and on P accumulation, where fertilization placed in autumn/winter increased this accumulation.